2018
DOI: 10.1017/sjp.2018.56
|View full text |Cite
|
Sign up to set email alerts
|

How Loneliness is Associated with Depressive Symptoms in Spanish College Students: Examining Specific Coping Strategies as Mediators

Abstract: In this study, we examined coping strategies as a mediator of the association between loneliness and depressive symptoms. A sample of 364 Spanish young adults (75.5% females) completed measures of loneliness, coping, and depressive symptoms. In general, results from computing correlations (controlling for gender) indicated that loneliness was negatively associated with the use of one engaged coping strategy (viz., problem solving) and positively associated with the use of disengaged coping strategies (e.g., pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…However, in the earlier time of the COVID-19 pandemic when death threats and negative emotions were diffused, individuals were more anxious of infecting the COVID-19 virus rather than social anxiety. In addition, studies have indicated that among the factors associated with loneliness, depression has the greatest impact ( Fuente et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the earlier time of the COVID-19 pandemic when death threats and negative emotions were diffused, individuals were more anxious of infecting the COVID-19 virus rather than social anxiety. In addition, studies have indicated that among the factors associated with loneliness, depression has the greatest impact ( Fuente et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal research has also demonstrated that loneliness predicts depression ( Chang, 2017 ), not only at a specific moment but also vertically in time ( Louise et al, 2010 ; Qualter et al, 2010 ; Vanhalst et al, 2012 ). Moreover, studies have revealed an association between loneliness and depressive symptoms ( Cacioppo et al, 2006 ; Chang, 2017 ) and shown that loneliness can predict a heightening of depressive symptoms over time ( Fuente et al, 2018 ). Recently, studies have revealed that loneliness has a significant effect on depression at a moderate level ( Erzen and Cikrikci, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study of coping strategies in isolation situations was previously carried out in the framework of the analysis of the following problems: loneliness [23,36], restrictions on communication related to hospitalization [22], migration [37] and imprisonment [6]. It has been shown that the depression level is mediated by feelings of loneliness and coping strategies used by a person.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the depression level is mediated by feelings of loneliness and coping strategies used by a person. In particular, loneliness reveals a negative correlation with strategies aimed at solving the problem and positively correlates with strategies aimed at avoiding the situation [24,26,36]. Social ties with the family and religious practices can facilitate social exclusion for migrants and refugees [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Danish survey among higher education students linked loneliness with increased levels of stress (Khalid, 2017). Additionally, increased feelings of loneliness among students in higher education have specifically been shown to be related to disturbed sleeping patterns (Hayley, Downey, Stough, Sivertsen, Knapstad & Øverland, 2017), learning burnout (Lin & Huang, 2012; Stoliker & Lafreniere, 2015), psychosocial stress (Sladek & Doane, 2015), depressive symptoms and suicidal behavior (Chang, Muyan & Hirsch, 2015; de la Fuente, Chang, Cardeñoso & Chang, 2018), greater anxiety, stress, depression and general mental health over time (Richardson, Elliott & Roberts, 2017), drop‐out (Rotenberg & Morrison, 1993), a poorer recognition memory, and decreased academic performance (Rosenstreich & Margalit, 2015). Additionally, being an international student increases the risk of experiencing loneliness (Jones, Lodder & Papadopoulos, 2019).…”
Section: Introductionmentioning
confidence: 99%